A Critique on the Book Strategic Management and Business Policy-Environmental Analysis and Strategy Formulation - Amir Reza Konjkav Monfared (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to review and critique the book Strategic Management and Business Policy by Thomas L. Wheelen and J. David Hunger. In the process of critique and evaluation of this book, the criteria and indicators of critique are used in accordance with the model provided by the Council for the Study of Humanities Texts and books. In this regard, the formal and content dimensions of the book have been studied and criticized with an analytical approach. The technical characteristics of the work such as cover design, page layout, font type, are considered desirable and appropriate, at the same time, the quality of some tables and diagrams is undesirable. The results of evaluating the qualitative content of the book showed that some words need to be revised in translation. Due to the main goals of the book, it was not necessary to present topics in a separate chapter. On the other hand, some issues such as mission statement, vision, and practical tools in the process of analyzing the environment and formulating strategy have not been considered. Considering the strengths and weaknesses of the book, it can be said that the content of the book meets the scientific and practical needs of the country. So, scholars can use its content to increase knowledge related to strategic management.